2015
DOI: 10.1530/rep-14-0559
|View full text |Cite
|
Sign up to set email alerts
|

Murine binder of sperm protein homolog 1: a new player in HDL-induced capacitation

Abstract: Binder of sperm (BSP) proteins are ubiquitous among mammals and are exclusively expressed in male genital tract. The main function associated with BSP proteins is their ability to promote sperm capacitation. In mice, two proteins (BSP protein homolog 1 (BSPH1) and BSPH2) have been studied. Using recombinant strategies, BSPH1 was found to bind to epididymal sperm membranes and promote sperm capacitation in vitro. The goal of this study was to evaluate the role of native murine BSPH1 protein in sperm capacitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…During epididymal transit and while still bound to sperm, BSPH1 is said to prevent movement of lipids in the sperm membrane and thereby protect the sperm from premature capacitation. When the sperm cell reaches the oviduct it comes in contact with high-density lipoproteins (HDLs) which interact with BSPH1 and can cause release of phospholipids and cholesterol from the sperm membrane (Plante & Manjunath 2015). This was shown for both mouse and human sperm, which displayed increased protein tyrosine phosphorylation after incubation with recombinant BSPH1.…”
Section: Binder Of Sperm Protein Homologmentioning
confidence: 99%
“…During epididymal transit and while still bound to sperm, BSPH1 is said to prevent movement of lipids in the sperm membrane and thereby protect the sperm from premature capacitation. When the sperm cell reaches the oviduct it comes in contact with high-density lipoproteins (HDLs) which interact with BSPH1 and can cause release of phospholipids and cholesterol from the sperm membrane (Plante & Manjunath 2015). This was shown for both mouse and human sperm, which displayed increased protein tyrosine phosphorylation after incubation with recombinant BSPH1.…”
Section: Binder Of Sperm Protein Homologmentioning
confidence: 99%
“…However, they have also been found to promote sperm capacitation in bulls, boars, humans and mice and such effects on capacitation are mediated by stimulation of sperm membrane cholesterol and phospholipid efflux in the presence of heparin or HDL, both components of follicular and oviductal fluids (for review see Manjunath and Thérien, 2002). Recently, it has been shown that antibodies against murine BSPH1 could block capacitation induced by HDLs, suggesting a specific interaction between HDL and BSPH1 (Plante and Manjunath, 2015b). Nevertheless, as the capacitation promoting effect is observed under conditions resembling the milieu of the female reproductive tract while in seminal fluid BSPs stabilize sperm membrane and prevent premature capacitation, it has been proposed that they are multifunctional proteins that employ different mechanisms to exert such effects (Plante et al ., 2016).…”
Section: Proteins Derived From Male Reproductive Tract That Interact mentioning
confidence: 99%
“…However, in vivo , physiological concentrations of BSPH1 are much lower than the concentrations of recombinant BSPH1 proteins used in in vitro experiments. Interestingly, recent data in mouse demonstrate that antibodies and Fabs specific against BSPH1 are able to inhibit capacitation and prevent tyrosine phosphorylation induced by HDL implying that BSPH1 could be essential for fertility (Plante & Manjunath, ). These results together suggest a mechanism in mouse and human similar to the one observed in ungulates where BSPH1 is added to the spermatozoa in the early steps of epididymal maturation and protects spermatozoa until they reach the oviduct.…”
Section: Role Of Bsp Family Proteins In Sperm Functionmentioning
confidence: 99%